Proposed Business Process Strategy to Increase the Number of Fresh Water Crayfish Production (Case Study: Jaring Emas Nusantara) (The Indonesian Journal of Business Administration, 2020)
Jaring Emas Nusantara (JEN) is a B2B business engaged in aquaculture. JEN was established on 24 May 2018. JEN is located in Banda Aceh. The commodities of this business activity are cultivation, trading, and supply. In lobster cultivation activities aim at seed production. Then in trading activities, the company accommodates the results of lobster cultivators and the catch of fishermen which will be re-selected by Jaring Emas Nusantara, lobsters that are ready to be sold and lobsters that can be cultivated.This study aims to find an effective business process strategy to increase the yield of Jaring Emas Nusantara lobster seed using qualitative methods. Literature study, internal and external analysis are then applied to analyze the current condition and position of the company. For internal analysis, Jaring Emas Nusantara will use RBV analysis, value chain analysis and VRIO analysis, while external analysis will use Porters Five Force, PESTLE analysis, and competitor analysis. The alternative business process strategy is then deepened by conducting in-depth interviews with several sources that are specialized in fisheries.The results of the study are based on internal and external analysis with a choice of strategies: SO, WO, ST, and WT. The key to the successful use of the TOWS matrix is to bring together internal and external factors to come up with a good alternative solution for the company to become the future strategy for the Jaring Emas Nusantara.The results of the interview data were processed and tested with recommendations for business process strategies that had been given by several sources specialized in fisheries. With the implementation of the business process strategy the Recirculating Aquaculture System becomes one of the business solutions that can be applied to freshwater crayfish, because it can increase production value, reduce production costs and be efficient. Then make a good time planning for the implementation of the strategy carried out by the company so that it runs in accordance with the preparation and readiness of the Jaring Emas Nusantara in developing new solutions based on the analysis of the problems that have been carried out.KEYWORDS: Business Process Strategy, Internal and External Research, RAS, Aquaculture, Fisheries